Процедура оценивания качества процесса принятия управленческих решений - Высочина, М. В. (Культура народов Причерноморья, 2014)
Качество процесса принятия управленческого решения определяет качество конечного результата – собственно управленческого решения. Обеспечение качества процесса принятия управленческих решений возможно при соблюдении определенных требований к этому процессу. Разработка действенного механизма принятия качественных управленческих решений строится на основе оценивания уровня соответствия процесса требованиям качества. Предложена процедура оценивания соответствия процесса принятия управленческих решений требованиям качества с применением инструментария квалиметрии и нечеткой логики. Разработана система показателей оценки соответствия процесса принятия управленческих решений требованиям качества. Якість процесу ухвалення управлінського рішення визначає якість кінцевого результату – власне управлінського рішення. Забезпечення якості процесу ухвалення управлінських рішень можливо при дотриманні певних вимог до цього процесу. Розробка дієвого механізму ухвалення якісних управлінських рішень ґрунтується на основі оцінювання рівня відповідності процесу вимогам якості. Запропоновано процедуру оцінювання відповідності процесу ухвалення управлінських рішень вимогам якості із застосуванням інструментарію кваліметрії і нечіткої логіки. Розроблено систему показників оцінювання відповідності процесу ухвалення управлінських рішень вимогам якості. The process of administrative decision-making plays a key role in the management activities. The quality of the process of administrative decision-making depends on the success of the whole enterprise in general. The quality of decision-making determines the quality of the final result – the administrative decisions. Administrative decision is considered from the standpoint of the process approach. Ensuring the quality of administrative decision-making is possible if the requirements for this process are certained. The structural elements of the system of requirements to the quality of the process of administrative decision-making were highlighted: the control of outputs of the process steps, methods and techniques, resource support of the process, professional and psychological qualities of the decision-maker. The proposed procedure for assessment of conformity of the process of managerial decision-making to the quality requirements using the tools of qualimetry and fuzzy logic. The system of indexes of estimation of conformity of the managerial decision-making to the quality requirements is developed.